2016
DOI: 10.1038/nplants.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Multi-country evidence that crop diversification promotes ecological intensification of agriculture

Abstract: Global food security requires increased crop productivity to meet escalating demand(1-3). Current food production systems are heavily dependent on synthetic inputs that threaten the environment and human well-being(2,4,5). Biodiversity, for instance, is key to the provision of ecosystem services such as pest control(6,7), but is eroded in conventional agricultural systems. Yet the conservation and reinstatement of biodiversity is challenging(5,8,9), and it remains unclear whether the promotion of biodiversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
300
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(305 citation statements)
references
References 28 publications
5
300
0
Order By: Relevance
“…In addition, better understanding of edge-biased distributions may be used to optimize deployments of anti-insect nets in the orchard industry (Castellano et al 2008). Finally, there is a growing body of literature on the potential use of banker plant systems (Zheng et al 2017;Gurr et al 2004Gurr et al , 2012Gurr et al , 2015Gurr et al , 2016Lu et al 2015;Zehnder et al 2007;Hossain et al 2002). In these agricultural systems, the agroecological landscape is manipulated through integration of special plants along crop banks.…”
Section: Potential Applications Of Edge-biased Distributions Into Insmentioning
confidence: 99%
“…In addition, better understanding of edge-biased distributions may be used to optimize deployments of anti-insect nets in the orchard industry (Castellano et al 2008). Finally, there is a growing body of literature on the potential use of banker plant systems (Zheng et al 2017;Gurr et al 2004Gurr et al , 2012Gurr et al , 2015Gurr et al , 2016Lu et al 2015;Zehnder et al 2007;Hossain et al 2002). In these agricultural systems, the agroecological landscape is manipulated through integration of special plants along crop banks.…”
Section: Potential Applications Of Edge-biased Distributions Into Insmentioning
confidence: 99%
“…For this reason, it is strongly advised not to spray rice fields with insecticides during the first 40 days after transplanting (Kenmore et al, 1984). The success of this heuristic has been borne out by several studies, and most recently by a convincing study from China (Gurr et al, 2016).…”
Section: Natural Pest Managementmentioning
confidence: 99%
“…Therefore, several strategies have been devised to restore natural enemies, increase their efficiency and also improve the resilience of rice ecosystems against perturbations -including resilience against climate change (Gurr, 2009;Gurr et al, 2016;Westphal et al, 2015;Horgan et al, 2016d). For example, in a comprehensive study, Kiritani (1999) indicated that most predators and parasitoids in Japanese rice fields were likely to increase the number of generations they achieved by 2 or 3 under average mean monthly temperature increases of 2°C, whereas most rice pests would only increase their generations by one.…”
Section: Natural Pest Managementmentioning
confidence: 99%
See 2 more Smart Citations